Synthesis of some ether derivatives of curcumin - Cường, Hồ Đức; Nga, Trương Thi Thanh; Vũ, Trần Khắc (Vietnam Journal of Chemistry, 2012)
The synthesis of new ether derivatives of curcumin (4a-c) via in situ two - step reaction and ester derivatives of of curcumin (6a-b) was performed in moderate to high yields. The structure of synthesized derivatives was confirmed by IR, 1H-NMR and 13C-NMR spectra.